Second‐to‐fourth digit ratio (2D:4D) is unrelated to measures of somatic reproductive effort among young men from Cebu, the Philippines. Issue 3 (27th March 2017) - Georgiev, Alexander V.; Ryan, Calen P.; Gettler, Lee T.; McDade, Thomas W.; Kuzawa, Christopher W.
Abstract: Objectives: A low second‐to‐fourth (2D:4D) digit ratio, a retrospective marker of high prenatal androgens, predicts increased investment in costly sexually dimorphic traits in men in some studies, although results are mixed. Here we test the hypothesis that the association of low 2D:4D ratios with increased muscularity and decreased adiposity depends on current testosterone (T) levels, such that digit ratio will be a particularly strong predictor of outcomes among men exhibiting a mating‐effort‐oriented endocrinological profile (high T). We also test the association between 2D:4D and somatic traits independently of T. Materials and methods: We related 2D:4D digit ratios, and their interaction with T, to handgrip strength, lean mass, arm muscle area, and skinfold thickness in a sample of young, childess men (20–22 y) from Cebu, Philippines ( N = 623). Results: Digit ratio did not significantly predict men's T‐dependent somatic traits. Interactions between 2D:4D and morning T, similarly, did not predict male muscularity or adiposity. Although two of the interactions were significant or marginally significant ( p < .1), after adjusting for multiple testing the evidence in support of our hypothesis was weak. Discussion: We found no evidence that 2D:4D predicted measures of somatic reproductive effort in this sample of young men from Cebu, who as a group could be considered mostly mating‐oriented. These relationships were also not contingent upon, or stronger, when considering the moderating effect of concurrent T levels. In this sample, 2D:4D was therefore either a poor proxy of prenatal androgen exposure or prenatal androgens had limited influence on adult somatic outcomes.